Bonding of Gold Nanoclusters on Graphene with and without Point Defects - Theo Pavloudis (Nanomaterials, 2020)
Hybrid nanostructures of size-selected nanoparticles (NPs) and 2D materials exhibit striking physical and chemical properties and are attractive for many technology applications. A major issue for the performance of these applications is device stability. In this work, we investigate the bonding of cuboctahedral, decahedral and icosahedral Au NPs comprising 561 atoms on graphene sheets via 103-atom scale ab initio spin-polarized calculations. Two distinct cases we considered: (i) the Au NPs sit with their (111) facets on graphene and (ii) the NPs are oriented with a vertex on graphene. In both cases, we compare the binding energies with and without a graphene vacancy under the NP. We find that in all cases, the presence of the graphene vacancy enhances the bonding of the NPs. Significantly, in the vertex-on-graphene case, the binding energy is considerably increased by several eVs and becomes similar to the (111) facet-on-graphene case. The strain in the NPs is found to be minimal and the displacement of the carbon atoms in the immediate neighborhood of the vacancy is on the 0.1 Å scale. The work suggests the creation of stable NP-graphene systems for a variety of electronic, chemical and photonic applications.